Direct observation of shift and ballistic photovoltaic currents - Burger, Aaron M. (Sci Adv, 2019)
The quantum phenomenon of shift photovoltaic current was predicted decades ago, but this effect was never observed directly because shift and ballistic currents coexist. The atomic-scale relaxation time of shift, along with the absence of a photo-Hall behavior, has made decisive measurement of shift elusive. Here, we report a facile, direct-current, steady-state method for unambiguous determination of shift by means of the simultaneous measurements of linear and circular bulk photovoltaic currents under magnetic field, in a sillenite piezoelectric crystal. Comparison with theoretical predictions permits estimation of the signature length scale for shift. Remarkably, shift and ballistic photovoltaic currents under monochromatic illumination simultaneously flow in opposite directions. Disentangling the shift and ballistic contributions opens the way for quantitative, fundamental insight into and practical understanding of these radically different photovoltaic current mechanisms and their relationship.